DETECTION OF RESISTANCE DETERMINANTS BY MOLECULAR ANALYSIS AMONG THE QUINOLONE RESISTANT SALMONELLA ENTERICA SEROVAR TYPHI ISOLATES FROM KANCHIPURAM - M P Sivasankaran; K Sujitha; Asgar Ali (International Journal of Medical Research, 2013)
Aim: To study the antimicrobial susceptibility pattern and detection of plasmid mediated quinolone resistance in Salmonella enteric serovar Typhi. Method: We collected 62 isolates from a tertiary care hospital in Kanchipuram from 2009–2011. All the isolates were subjected to antimicrobial susceptibility testing by Kirby-Bauer disk diffusion method and broth microdilution method was used to determine minimum inhibitory concentration of ciprofloxacin and nalidixic acxid. Then the strains were amplified for the presence of plasmid mediated quinolone resistance (PMQR) gene. Result: All the 62 isolates were found to be nalidixic acid resistant strains (NARST) and susceptible to ciprofloxacin. Few isolates showed resistance to ampicillin, co-trimoxazole, tetracycline and chloramphenicol. None of the isolates amplified for PMQR gene. Discussion: The present study indicates the higher prevalence of NARST and there may be a low-level rate of dissemination of Qnr determinants among human Salmonella isolates.